The Effect of The Addition of Natural Preservative Substance Concentration of Arenga pinnata Sap During Storage on the Quality of Liquid Palm Sugar - Ricky Fauzi Lubis; Rona Joharmi Nainggolan; Mimi Nurminah (Universitas Sumatera Utara, 2013)
The research was conducted to determine the effect of the addition of natural preservative substance concentration of Arenga pinnata sap during storage on the quality of liquid palm sugar. The research had been performed using a completely randomized design with two factors, i.e. natural preservative substance concentration which is jackfruit stalk (N) : (2%), (4%), (6%), and (8%) and storage time (L) : (0, 1, 2, and 3 days). Parameters analyzed were pH, total acid, total sugars, total soluble solid (TSS) of Arenga pinnata sap, sensory characteristics (color and aromatic) of Arenga pinnata sap, TSS of liquid palm sugar, yield, sensory characteristics (color, aromatic, and flavor) of liquid palm sugar. The results showed that the natural preservative substance concentration had highly significant effect on all parameters. Storage time had highly significant effect on all parameters. Interaction of both factors had highly significant effect on TSS of Arenga pinnata sap, sensory characteristics color of Arenga pinnata sap, and TSS of liquid palm sugar, had significant effect on pH and total acid, and had no significant effect on total sugars, sensory characteristics aromatic of Arenga pinnata sap, yield, and sensory characteristics (color, aromatic, and flavor) of liquid palm sugar. Natural preservative substance concentration of 6% was the best treatment for the quality of liquid palm sugar. Key words : Arenga pinnata sap, natural preservative substance, liquid palm sugar, storage time